Carbonaceous material for electrochemical device and method for producing the same, negative electrode for electrochemical device, and electrochemical device
By controlling multiple physical characteristics of carbonaceous materials, carbonaceous materials suitable for use in electrochemical equipment are prepared, which solves the problem of increasing electrode density in the prior art, resulting in an irreversible capacity increase, and achieves high density and high efficiency electrochemical performance.
Patent Information
- Application Number
- CN202080070722.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-10-10
- Filing Date
- 2020-10-06
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2040-10-06
AI Technical Summary
In the prior art, when the particle size of carbonaceous material is reduced to increase the electrode density, it is easy to increase the irreversible capacity and reduce the charge and discharge efficiency, and the sufficient increase of the energy density cannot be achieved.
By controlling the particle size distribution, particle shape, aggregation and fluidity of carbonaceous materials, composite indicators reflecting these factors are used to ensure that the specific surface area is below 23m2/g, the flow energy during ventilation is above 40mJ and below 210mJ, the particle size distribution index D50/D10 ≥ 1.9, and the average surface spacing d002 ≥ 0.36nm of the (002) plane is used to prepare carbonaceous materials suitable for electrochemical equipment.
The electrode materials of electrochemical equipment that ensure high electrode density and high capacity while suppressing the increase of irreversible capacity is achieved, thereby improving the density and charge and discharge efficiency of the electrodes.
Smart Images

Figure GDA0004655416420000101 
Figure GDA0004655416420000191 
Figure GDA0004655416420000192
Abstract
Description
Technical Field
[0001] The present invention relates to a carbonaceous material for an electrochemical device and a method for producing the same, as well as a negative electrode for an electrochemical device and an electrochemical device comprising the carbonaceous material for an electrochemical device. Background Art
[0002] In recent years, with the popularization of small portable terminals such as mobile phones and notebook personal computers, electric vehicles and hybrid vehicles, various electrochemical devices have been developed. Among them, non-aqueous electrolyte secondary batteries using carbonaceous materials represented by lithium ion secondary batteries as negative electrodes are widely used, and are small and lightweight for vehicle-mounted uses, but on the other hand, it is required to improve energy density. For example, in patent document 1, a carbonaceous material that can be used in a non-aqueous electrolyte secondary battery with high electrode density, excellent input-output characteristics and cycle characteristics is disclosed.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent document 1: Japanese Patent Application Publication No. 2017-073325. Summary of the invention
[0006] Problems to be solved by the invention
[0007] However, if the particle size of the carbonaceous material is reduced as in Patent Document 1, the specific surface area becomes larger, so the irreversible capacity of the non-aqueous electrolyte secondary battery using such a carbonaceous material as an electrode is easily increased, and the charge and discharge efficiency is reduced, thereby failing to achieve a sufficient increase in energy density. Therefore, it is necessary to develop a carbonaceous material suitable for obtaining an electrode for an electrochemical device with a small irreversible capacity while ensuring a high electrode density.
[0008] In view of the above problems, an object of the present invention is to provide a carbonaceous material suitable as an electrode material for an electrochemical device that can suppress an increase in irreversible capacity and ensure high electrode density and high capacity, and a method for producing the same.
[0009] Means for solving problems
[0010] The inventors of the present invention have repeatedly studied carbonaceous materials in detail in order to solve the above-mentioned problems. As a result, in order to ensure high electrode density while suppressing the increase of irreversible capacity, in addition to controlling the particle size of the carbonaceous material, various factors such as particle size distribution, shape of each particle, agglomeration, fluidity, etc. are involved in combination. It is important to control them in a good balance. Indicators that reflect these factors in combination have been discovered, thereby completing the present invention.
[0011] That is, the present invention includes the following preferred aspects.
[0012] [1] A carbonaceous material for an electrochemical device having a specific surface area of 23 m2 as measured by the BET method 2 / g or less, and the flow energy (AE) during ventilation measured by a powder rheometer is 40 mJ or more and 210 mJ or less.
[0013] [2] The carbonaceous material according to [1], wherein the average particle size D at which the cumulative volume from the fine particle side reaches 50% in the particle size distribution measured by a laser scattering method is 50 The particle size D is 1 μm or more and 50 μm or less and is based on 10% of the cumulative volume calculated from the microparticle side. 10 The average particle size D 50 The particle size distribution index D 50 / D 10 It is above 1.9.
[0014] [3] The carbonaceous material according to [1] or [2], wherein the average interplanar spacing d of the (002) planes calculated using the Bragg formula based on wide-angle X-ray diffraction is 002 It is above 0.36nm.
[0015] [4] The carbonaceous material according to any one of [1] to [3] above, wherein the carbonaceous material is derived from a plant.
[0016] [5] A negative electrode for an electrochemical device, comprising the carbonaceous material according to any one of [1] to [4] above.
[0017] [6] An electrochemical device comprising the negative electrode for an electrochemical device according to [5].
[0018] [7] A method for producing a carbonaceous material, comprising:
[0019] A step of subjecting the carbon precursor or the calcined carbon precursor to a primary pulverization;
[0020] A step of classifying the once pulverized carbon precursor or the calcined carbon precursor; and
[0021] a step of secondary pulverizing the classified carbon precursor or the calcined carbon precursor; and
[0022] The step of calcining the carbon precursor.
[0023] [8] The method according to [7], wherein in the first pulverization step, the average particle size D 50 The carbon precursor or the calcined product of the carbon precursor is pulverized to a size of 2.7 μm or more and 300 μm or less.
[0024] [9] The method for producing a carbonaceous material according to [7] or [8] above, wherein in the classification step, the once-crushed carbon precursor or the calcined carbon precursor is classified in such a manner that the content of particles having a particle size of 1 μm or less is 6 volume % or less.
[0025]
[10] The production method according to any one of [7] to [9], wherein in the secondary pulverization step, the average particle size D 50 The particle size D is 1 μm or more and 50 μm or less and accounts for 10% of the total volume. 10 The average particle size D 50 The particle size distribution index D 50 / D 10 The classified carbon precursor or the calcined product of the carbon precursor is pulverized so as to reach 1.9 or more.
[0026] Effects of the Invention
[0027] According to the present invention, it is possible to provide a carbonaceous material suitable as an electrode material for an electrochemical device that can suppress an increase in irreversible capacity and ensure high electrode density and high capacity, and a method for producing the same. DETAILED DESCRIPTION
[0028] Hereinafter, embodiments of the present invention will be described in detail, but the present invention is not limited thereto.
[0029] [Carbonaceous materials]
[0030] The BET specific surface area of the carbonaceous material of the present invention is 23 m 2 / g or less. If the BET specific surface area is greater than 23m 2 / g, when used as an electrode material, the area for reaction with the electrolyte becomes larger, so the irreversible capacity increases, resulting in a decrease in discharge capacity. From the perspective of effectively suppressing the increase in irreversible capacity, the BET specific surface area is preferably 20 m 2 / g or less, more preferably 18m 2 / g or less, more preferably 16m 2 When the carbonaceous material is used as an electrode material, the BET specific surface area is preferably 2 m 2 / g or more, more preferably 3m 2 / g or more, more preferably 4m 2 For example, by increasing the calcination temperature or extending the calcination time, there is a tendency for the specific surface area to become smaller, and the BET specific surface area can be controlled to be within the above-mentioned desired range by adjusting the calcination temperature and calcination time of the carbon precursor of the carbonaceous material.
[0031] In the present invention, the BET specific surface area can be calculated by a nitrogen adsorption method, for example, by the method described in Examples below.
[0032] The aerated flow energy of the carbonaceous material of the present invention measured by a powder rheometer is greater than 40mJ and less than 210mJ. The aerated flow energy (AE: Aerated Energy, hereinafter also referred to as "AE") measured by a powder rheometer represents the powder state when the carbonaceous material is filled. If the AE of the carbonaceous material is below the above upper limit and above the lower limit, the density of the electrode obtained from the carbonaceous material can be increased, and the capacity per unit volume can be increased. On the other hand, if there are excessive microparticles, there is a tendency for AE to increase, but by setting AE to below the above upper limit, the coating properties of the negative electrode are improved, and good charge and discharge efficiency is obtained.
[0033] In the present invention, AE is preferably 40 mJ or more, more preferably 50 mJ or more, and even more preferably 55 mJ or more, and is preferably less than 210 mJ, more preferably 205 mJ or less, and even more preferably 200 mJ or less.
[0034] In order to obtain an electrode for an electrochemical device with a small irreversible capacity while having a high electrode density, increasing the filling amount of the carbonaceous material in the electrode can be an effective means on the basis of controlling the specific surface area to a moderate range. However, the electrode density cannot be simply controlled by, for example, the tap density, which can generally be an indicator of the filling amount, etc. The particle size, particle size distribution, specific surface area, shape of the particles of the carbonaceous material, agglomeration, fluidity and other various factors of the carbonaceous material are involved in the complex participation, and it is important to control them in a good balance. Therefore, even if the above-mentioned various factors are used as indicators, it is difficult to control the electrode density when the carbonaceous material is filled.
[0035] In contrast, the present invention finds that the above-mentioned AE compositely reflects various elements of carbonaceous materials and is a parameter closely related to electrode density, and uses it as a new indicator. As a result, the electrode density when filling the carbonaceous material can be correctly and easily controlled, and a carbonaceous material suitable for obtaining an electrode for an electrochemical device with a small irreversible capacity while having a high electrode density can be provided. In other words, AE does not simply reflect the various elements such as the chemical state, agglomeration, fluidity, etc. caused by the particle size distribution of the carbonaceous material, the shape of each particle, the surface functional groups of the carbonaceous material, etc., but compositely reflects the characteristics caused by these elements. Therefore, for example, the control of the electrode density that is difficult to perform only by adjusting the particle size distribution can be correctly and easily performed using AE as an indicator.
[0036] In the present invention, AE is measured by a powder rheometer, which is a powder flow analysis device. Specifically, for the sample powder filled in the device, the movement of the knife corresponding to the knife height required to move the knife provided in the device is measured as the energy value (J) when air is ventilated from the bottom of the device at a ventilation rate of 2 mm / sec. For example, as a measuring device for AE, a powder rheometer FT4 manufactured by Freeman Technolog Co., Ltd. can be used.
[0037] The measurement of AE in the present invention can be calculated by, for example, the method described in the embodiments described later. Specifically, based on the powder rheometer FT4 manufactured by Freeman Technolog Co., Ltd., air is ventilated from the bottom of the device at a ventilation rate of 2 mm / sec, and a knife is rotated at a constant blade tip speed while entering a container filled with powder, and the vertical stress F is measured by the load sensor at the bottom of the device, and the rotational torque T is measured by the upper torque meter. From the vertical stress F, the rotational torque T and the knife height at this time, the energy required for the knife to move in the powder can be calculated. The knife radius (also called the knife blade diameter) is recorded as R, the spiral angle of the knife tip movement is recorded as α°, and the movement energy of the knife corresponding to the knife height is recorded as the flow energy during ventilation (AE). That is, the flow energy during ventilation (AE) is calculated according to the following formula: AE=T / (Rtanα)+F. In the powder rheometer FT4 manufactured by Freeman Technolog Co., Ltd., α=5°, R=48 mm, the diameter of the container filled with powder is 50 mm, and the volume of the container is 160 cm 3 (See Hiramura Yukiyoshi, "Evaluation of rheological properties and investigation of fluidity of powders", Journal of the Powder Engineering Society, 2017, Vol. 54, No. 9, p604-608.) For example, 120 mL of powder is filled until the flat top of the container, air is ventilated from the bottom of the device at a ventilation rate of 2 mm / sec, and the blades are rotated at a speed of 100 mm / sec at the tip to enter the device, thereby calculating the flow energy (AE) during ventilation.
[0038] In the carbonaceous material of the present invention, AE can be controlled by controlling the conditions, sequence, number, etc. of the pulverization step and the classification step in the manufacturing method of the carbonaceous material. In this case, for example, in the manufacturing process of the carbonaceous material, AE can be confirmed in appropriate stages such as each pulverization step and the classification step, and the pulverization conditions and the classification conditions can be controlled at the same time. In addition, AE can also be controlled by mixing a carbonaceous material with a smaller particle size and a carbonaceous material with a larger particle size in an appropriate ratio.
[0039] In the present invention, the average particle size D at which the cumulative volume from the fine particle side reaches 50% in the particle size distribution of the carbonaceous material measured by a laser scattering method is 50 It is preferably 1 μm or more and 50 μm or less. 50When the particle size is within the above range, the increase in specific surface area can be suppressed, the irreversible capacity can be reduced, and the electrode polarization can be facilitated. 50 It is more preferably 1.5 μm or more, further preferably 2 μm or more, particularly preferably 2.5 μm or more, and more preferably 30 μm or less, further preferably 15 μm or less, particularly preferably 10 μm or less, and most preferably 8 μm or less.
[0040] In the present invention, the average particle size D 50 It can be measured by a laser scattering method, and can be measured and calculated by, for example, the method described in Examples below.
[0041] In the carbonaceous material of the present invention, the particle size D at which the cumulative volume from the fine particle side reaches 10% is 10 The average particle size D 50 The particle size distribution index D 50 / D 10 It is preferably 1.9 or more. 50 / D 10 When the particle size distribution index D is greater than the above lower limit, the AE of the carbonaceous material is likely to fall within the above specific range, and the density of the electrode obtained from the carbonaceous material is likely to be high, and the capacity per unit volume is likely to be increased. 50 / D 10 It is more preferably greater than 1.9, further preferably 2.0 or more, particularly preferably 2.1 or more, and particularly preferably 2.5 or more. It is preferably 10.0 or less, more preferably 5.0 or less, further preferably 4.5 or less, and particularly preferably 4.0 or less.
[0042] Particle size distribution index D 50 / D 10 The D can be measured and calculated by laser scattering method. 10 and D 50 Figure it out.
[0043] The average interplanar spacing d of the (002) plane of the carbonaceous material of the present invention calculated by wide-angle X-ray diffraction using the Bragg formula is 002 It is preferably 0.36 nm or more, more preferably 0.37 nm or more, and even more preferably 0.38 nm or more. It is also preferably 0.42 nm or less, more preferably 0.41 nm or less, and even more preferably 0.40 nm or less. If the average interplanar spacing d of the (002) plane is 002 When the average interplanar spacing is within the above range, good input and output characteristics are exhibited. The average interplanar spacing can be controlled by adjusting the calcination temperature of the carbonaceous material or the carbon precursor of the carbonaceous material.
[0044] [Method for producing carbonaceous material]
[0045] The carbonaceous material of the present invention can be produced by, for example, a method comprising the following steps:
[0046] A step of subjecting the carbon precursor or the calcined carbon precursor to a primary pulverization;
[0047] A step of classifying the once pulverized carbon precursor or the calcined carbon precursor; and
[0048] a step of secondary pulverizing the classified carbon precursor or the calcined carbon precursor; and
[0049] The step of calcining the carbon precursor.
[0050] Therefore, the present invention also targets a method for producing a carbonaceous material including the above steps.
[0051] After the coarse-grained carbon precursor or the calcined product of the carbon precursor (hereinafter both are also collectively referred to as "carbon precursor, etc.") is crushed once, the fine powder is removed by classification, and then the AE of the carbonaceous material is controlled to the above-mentioned desired range by secondary crushing to the desired particle size. Therefore, in the above method, the steps of primary crushing, classification and secondary crushing are performed in sequence. On the other hand, the carbon precursor is not melted by calcination, so the average particle size of the carbon precursor remains substantially unchanged before and after calcination. Therefore, there is no particular limitation on the order of performing the above-mentioned crushing and classification steps and the calcination step, and the above-mentioned crushing and classification steps can be performed on the carbonaceous material before calcination, and the above-mentioned crushing and classification steps can also be performed on the carbonaceous material after calcination (that is, the calcined product of the carbon precursor).
[0052] In the present invention, the step of subjecting the carbon precursor or the calcined product of the carbon precursor to a primary pulverization (hereinafter also referred to as the "primary pulverization step") is a step of pulverizing the coarse particles of the carbon precursor etc. into fine particles. The average particle size of the carbon precursor etc. subjected to the primary pulverization can be appropriately determined according to the carbon material and the carbon precursor as the raw material, and is not particularly limited. From the viewpoint of easy control to a desired particle size and excellent handling properties, the average particle size D of the carbon precursor etc. subjected to the primary pulverization is preferably 0.0447 W / cm2. 50 The thickness is usually 100 μm or more and 10000 μm or less, preferably 200 μm or more, more preferably 400 μm or more, and preferably 8000 μm or less, more preferably 5000 μm or less.
[0053] It should be noted that the average particle size D of the carbon precursor etc. after the primary pulverization is 50 The average particle size D of the carbonaceous material of the present invention 50 The measurement of can also be carried out by laser scattering method.
[0054] In one embodiment of the present invention, in the primary pulverization step, the average particle size D 50The carbon precursor is crushed in such a way that the particle size reaches 2.7 μm or more and 300 μm or less. As previously described, the AE of the carbonaceous material is determined by a combination of many factors, such as the particle size, particle size distribution, shape, and chemical state caused by the surface functional groups of the carbonaceous material. Therefore, controlling the particle size of the carbon precursor in the first crushing does not directly determine the AE of the obtained carbonaceous material. However, by setting the particle size of the carbon precursor after the first crushing to the above range, it is easy to obtain a carbonaceous material with an AE in the range of 40 mJ or more and 210 mJ or less through the subsequent classification and secondary crushing steps. In the present invention, the average particle size D of the carbon precursor after the first crushing is 50 The thickness is preferably 3 μm or more, more preferably 4 μm or more, and is preferably 200 μm or less, more preferably 150 μm or less.
[0055] In the present invention, the primary pulverization step may be performed once or in multiple steps. In this specification, when pulverization is performed in multiple steps, the pulverization step performed before the first classification step of classifying the pulverized carbon precursor etc. is referred to as the primary pulverization step.
[0056] The pulverizer used in the primary pulverization step is not particularly limited, and for example, a jet mill, a ball mill, a bead mill, a hammer mill or a rod mill etc. can be used. As the pulverizer, one kind can be used, or two or more kinds can be used in combination. The method of pulverizing particles by contacting each other as represented by a jet mill has a long pulverization time, and the volumetric efficiency is easily reduced. Therefore, from the viewpoint of pulverization efficiency, it is preferably a method of pulverizing in the coexistence of a pulverization medium such as a ball mill or a bead mill. A bead mill is also suitable in that it can avoid the mixing of impurities from the pulverization medium. Among them, it is easy to take out from the pulverized material and it is easy to suppress the excess pulverization of carbon precursors, etc., so a pulverizing device with a classification mechanism is more preferred.
[0057] When a ball mill or a bead mill is used as a pulverizer, the material of the medium (balls or beads) is not particularly limited, and organic polymer compounds such as polyamide, inorganic oxides such as alumina, silica, titanium oxide, and zirconium oxide can be used. From the viewpoint of difficulty in generating contamination from the medium and easy shortening of the pulverization time, the medium is preferably alumina or zirconium oxide. The filling rate of the medium in the pulverizer is not particularly limited, but from the viewpoint of easily suppressing irregular shapes during pulverization, it is preferably 10 to 90%, more preferably 20 to 80%. The pulverization time can be appropriately determined in a manner that the desired particle size can be pulverized according to the particle size of the carbon precursor, etc., which is the raw material, the type of pulverizer used, etc.
[0058] The pulverization may be either wet pulverization or dry pulverization. From the viewpoint of suppressing surface oxidation of the carbon precursor and the like, dry pulverization is preferred.
[0059] The method for producing a carbonaceous material of the present invention includes a step of classifying a carbon precursor etc. after primary pulverization. This step is a step of removing a fine powder portion from the carbon precursor etc. after primary pulverization to control the particle size of the carbon precursor etc. By reducing the content of particles having a particle size that deviates significantly from the average particle size generated from the primary pulverization, especially particles having a small particle size that deviates significantly from the average particle size, it is possible to suppress excessive pulverization and suppress the increase in irreversible capacity due to an increase in specific surface area.
[0060] In one embodiment of the present invention, in the classification step after the primary pulverization step, the particles having a particle size of 1 μm or less are preferably classified in a manner such that the content of the particles is 6% by volume or less, more preferably 5% by volume or less, and further preferably 3% by volume or less. Particles having a particle size of 1 μm or less are removed from the carbon precursor after the primary pulverization, thereby suppressing excessive pulverization and suppressing the increase in irreversible capacity caused by the increase in specific surface area. It should be noted that the content of particles having a particle size of 1 μm or less after the classification step is as low as possible and may be 0% by volume.
[0061] In the classification step, as a method for classifying the carbon precursor, etc. (controlling the particle size of the carbon precursor, etc.), for example, a method of removing microparticles with a particle size of less than 1 μm contained in the carbon precursor, etc. after the primary crushing, a method of repeatedly crushing in a manner with a slightly larger average particle size, taking out large particles contained in the carbon precursor, etc. after the primary crushing in a manner to achieve a desired average particle size, and crushing the large particles again to obtain a desired average particle size, etc. If it is the latter method, the carbonaceous material of the present invention that does not contain more than a specified amount of microparticles can be manufactured with higher productivity.
[0062] There are no particular restrictions on the classification method, and examples thereof include classification using a sieve, wet classification, and dry classification. As a wet classifier, for example, a classifier using the principles of gravity classification, inertial classification, hydraulic classification, centrifugal classification, etc. can be cited. As a dry classifier, a classifier using the principles of sedimentation classification, mechanical classification, centrifugal classification, etc. can be cited. From the viewpoint of economy, it is preferred to use a dry classification device. In addition, the primary crushing and / or the secondary crushing step and the classification step described later can also be performed using one device.
[0063] The method for manufacturing a carbonaceous material of the present invention includes a step of performing secondary pulverization on the above-mentioned classified carbon precursor, etc. (hereinafter also referred to as "secondary pulverization step"). There is a tendency that the AE of the carbonaceous material obtained by classifying the carbon precursor, etc. after the primary pulverization and performing secondary pulverization on the carbon precursor, etc. after the removal of fine powder, becomes higher, which can increase the density of the electrode made using the carbonaceous material.
[0064] In one embodiment of the present invention, in the secondary pulverization step, the average particle size D 50 The particle size D is 1 μm or more and 50 μm or less and accounts for 10% of the total volume. 10 The average particle size D 50 The particle size distribution index D 50 / D 10 The classified carbon precursor etc. is crushed in a manner to reach 1.9 or more. The AE of the carbonaceous material is determined based on many factors such as the particle size, particle size distribution, shape, and chemical state caused by the surface functional groups of the carbonaceous material. Therefore, the control of the particle size of the carbon precursor etc. in the secondary crushing does not directly determine the AE of the obtained carbonaceous material, but by setting the particle size of the carbon precursor etc. after the secondary crushing to the above range, there is a tendency for the AE of the carbonaceous material to be improved, and it is easy to control the AE of the obtained carbonaceous material to be in the range of 40 mJ or more and 210 mJ or less.
[0065] In the present invention, the secondary pulverization step can be performed once or multiple times. It should be noted that in this specification, when pulverization is performed multiple times, the pulverization step performed after the first classification is recorded as the secondary pulverization step, and when further classification is performed thereafter, the pulverization step performed until the classification is recorded as the secondary pulverization step. The pulverizer, pulverization time, pulverization conditions, etc. that can be used in the secondary pulverization step can be the same as those in the primary pulverization step, and can be appropriately selected according to the desired particle size, particle size distribution, specific surface area, AE, etc.
[0066] In addition to the above-mentioned steps of primary pulverization, classification and secondary pulverization, the method for manufacturing the carbonaceous material of the present invention may also include further pulverization and / or classification steps as long as the desired AE and specific surface area are obtained. It is preferred that the final step among the pulverization step and classification step included in the step of obtaining the carbonaceous material is a pulverization step. After the secondary pulverization or subsequent pulverization is implemented, by substantially not performing classification, the final carbonaceous material is formed into a state containing particles with a smaller particle size, and can have a moderate breadth in the particle size distribution. As a result, the AE of the carbonaceous material easily reaches a range of more than 40mJ and less than 210mJ, which can increase the filling amount when filling the carbonaceous material and can increase the electrode density.
[0067] By calcining the carbon precursor after the above-mentioned primary crushing, classification and secondary crushing, the carbonaceous material of the present invention can be obtained. In addition, when the carbon precursor before the above-mentioned primary crushing is calcined, the carbonaceous material of the present invention can be obtained by subjecting the calcined carbon precursor (i.e., the calcined product of the carbon precursor) to the above-mentioned primary crushing, classification and secondary crushing.
[0068] The calcination (hereinafter also referred to as "main calcination") is not particularly limited to the carbon precursor before the primary pulverization and the carbon precursor after the secondary pulverization, and can be carried out according to the usual calcination process. By performing the main calcination, a carbonaceous material for electrochemical devices such as non-aqueous electrolyte secondary batteries can be obtained. The main calcination step is a step of heating the carbon precursor to remove the volatile components contained in the carbon precursor for constructing a carbon skeleton.
[0069] The calcination temperature of the main calcination is usually 800 to 1500° C., preferably 850 to 1350° C., and more preferably 900 to 1300° C. The main calcination is preferably carried out in an inert gas atmosphere. As the inert gas, nitrogen, argon, etc. can be mentioned, and the main calcination can also be carried out in an inert gas containing a halogen gas. The main calcination can be carried out under reduced pressure, for example, it can be carried out below 10 kPa. The calcination time of the main calcination is not particularly limited, for example, it is 0.05 to 10 hours, preferably 0.05 to 8 hours, and more preferably 0.05 to 6 hours.
[0070] In the present invention, when the carbon precursor is derived from plants, volatile organic matter can be mixed in the carbon precursor and calcined. By calcining the mixture of the carbon precursor and the volatile organic matter, the specific surface area of the obtained carbonaceous material can be reduced. The mechanism is not explained in detail, but it can be considered as follows. However, the present invention is not limited by the following description. It can be considered that by mixing and calcining the carbon precursor derived from plants and the volatile organic matter, a carbonaceous film obtained by heat treatment of volatile organic matter is formed on the surface of the carbon precursor derived from plants. Through the carbonaceous film, the specific surface area of the carbonaceous material generated by the carbon precursor derived from plants is reduced, and the formation reaction of the film called SEI (Solid Electrolyte Interphase, solid electrolyte intermediate phase) caused by the reaction of the carbonaceous material and lithium is suppressed, so it can be expected to reduce the irreversible capacity. In addition, the generated carbonaceous film can also be doped and dedoped with lithium, so the effect of increasing capacity can also be expected.
[0071] As volatile organic substances, for example, thermoplastic resins and low molecular weight organic compounds can be mentioned. Specifically, as thermoplastic resins, polystyrene, polyethylene, polypropylene, poly(meth)acrylic acid, and poly(meth)acrylates can be mentioned. It should be noted that in this specification, (meth)acryloyl refers to the general term for acryloyl and methacryloyl. As low molecular weight organic compounds, toluene, xylene, mesitylene, styrene, naphthalene, phenanthrene, anthracene, and pyrene can be mentioned. It is preferred that the substance that does not activate the surface oxidation of the carbon precursor when volatilizing or thermally decomposing at the calcination temperature is preferred, so as thermoplastic resins, polystyrene, polyethylene, and polypropylene are preferred. As low molecular weight organic compounds, further from the viewpoint of safety, it is preferred that the volatility is small at room temperature, and naphthalene, phenanthrene, anthracene, pyrene, etc. are preferred.
[0072] In one embodiment of the present invention, as thermoplastic resins, olefin resins, styrene resins, and (meth) acrylic resins can be cited. As olefin resins, polyethylene, polypropylene, random copolymers of ethylene and propylene, block copolymers of ethylene and propylene, etc. can be cited. As styrene resins, polystyrene, poly(α-methylstyrene), copolymers of styrene and (meth) acrylic acid alkyl esters (the number of carbon atoms of the alkyl group is 1 to 12, preferably 1 to 6), etc. can be cited. As (meth) acrylic resins, polyacrylic acid, polymethacrylic acid, and (meth) acrylic acid alkyl ester polymers (the number of carbon atoms of the alkyl group is 1 to 12, preferably 1 to 6), etc. can be cited.
[0073] In one embodiment of the present invention, as a low molecular organic compound, for example, a hydrocarbon compound having 1 to 20 carbon atoms can be used. The number of carbon atoms of the hydrocarbon compound is preferably 2 to 18, more preferably 3 to 16. The hydrocarbon compound may be a saturated hydrocarbon compound or an unsaturated hydrocarbon compound, and may be a chain hydrocarbon compound or a cyclic hydrocarbon compound. In the case of an unsaturated hydrocarbon compound, the unsaturated bond may be a double bond or a triple bond, and the number of unsaturated bonds contained in one molecule is not particularly limited. For example, the chain hydrocarbon compound is an aliphatic hydrocarbon compound, and linear or branched alkanes, alkenes, or alkynes can be cited. As a cyclic hydrocarbon compound, an alicyclic hydrocarbon compound (such as cycloalkanes, cycloalkenes, cycloalkynes) or an aromatic hydrocarbon compound can be cited. Specifically, as an aliphatic hydrocarbon compound, methane, ethane, propane, butane, pentane, hexane, octane, nonane, decane, ethylene, propylene, butene, pentene, hexene and acetylene can be cited. Examples of alicyclic hydrocarbon compounds include cyclopentane, cyclohexane, cycloheptane, cyclooctane, cyclononane, cyclopropane, cyclopentene, cyclohexene, cycloheptene, cyclooctene, decahydronaphthalene, norbornene, methylcyclohexane, and norbornadiene. Further, examples of aromatic hydrocarbon compounds include monocyclic aromatic compounds such as benzene, toluene, xylene, mesitylene, isopropylbenzene, butylbenzene, styrene, α-methylstyrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, vinylxylene, p-tert-butylstyrene, and ethylstyrene, and condensed polycyclic aromatic compounds having 3 to 6 rings such as naphthalene, phenanthrene, anthracene, and pyrene. Preferably, the condensed polycyclic aromatic compounds are used, and more preferably, naphthalene, phenanthrene, anthracene, or pyrene. Here, the aforementioned hydrocarbon compound may have an arbitrary substituent. The substituent is not particularly limited, and examples thereof include alkyl groups having 1 to 4 carbon atoms (preferably alkyl groups having 1 to 2 carbon atoms), alkenyl groups having 2 to 4 carbon atoms (preferably alkenyl groups having 2 carbon atoms), and cycloalkyl groups having 3 to 8 carbon atoms (preferably cycloalkyl groups having 3 to 6 carbon atoms).
[0074] From the viewpoint of avoiding the ease of mixing and the bias, the volatile organic matter is preferably in a solid state at room temperature, and more preferably a thermoplastic resin such as polystyrene, polyethylene or polypropylene which is solid at room temperature, or a low molecular organic compound such as naphthalene, phenanthrene, anthracene or pyrene which is solid at room temperature. It is preferred that the substance does not activate the surface oxidation of the plant-derived carbon precursor when thermally decomposed at the volatilization and calcination temperature, so as a thermoplastic resin, olefin resins and styrene resins are preferred, and polystyrene, polyethylene and polypropylene are more preferred. As a low molecular organic compound, it is further preferred that the volatility is small at room temperature in terms of safety, so a hydrocarbon compound having 1 to 20 carbon atoms is preferred, and a condensed polycyclic aromatic compound is more preferred, and naphthalene, phenanthrene, anthracene or pyrene is further preferred. Further, from the viewpoint of the ease of mixing with the carbon precursor, a thermoplastic resin is preferred, an olefin resin and a styrene resin are more preferred, polystyrene, polyethylene, polypropylene are further preferred, and polystyrene and polyethylene are particularly preferred.
[0075] From the viewpoint of stable operation of the calcining machine, the volatile organic matter is an organic matter having a residual carbon rate preferably lower than 5% by mass, more preferably lower than 3% by mass. The residual carbon rate in the present invention is preferably a residual carbon rate in the case of ashing at 800°C. The volatile organic matter is preferably a substance that produces volatile substances (e.g., hydrocarbon gases, coal components) that can reduce the specific surface area of the carbon precursor manufactured from plant-derived coke. In addition, from the viewpoint of maintaining the properties of the carbonaceous material generated after calcination, the residual carbon rate is preferably lower than 5% by mass. If the residual carbon rate is lower than 5%, it is difficult to produce carbonaceous materials with different local properties.
[0076] The residual carbon rate can be determined by quantifying the carbon content of the residual component after the sample is subjected to strong heating in an inert gas. Strong heating means that about 1g of volatile organic matter (its exact mass is recorded as W1(g)) is added to a crucible, and the crucible is heated from room temperature to 800°C at a heating rate of 10°C / min in an electric furnace while 20 liters of nitrogen are circulated for 1 minute, and then strong heating is applied at 800°C for 1 hour. The residue at this time is recorded as the strong heating residual component, and its mass is recorded as W2(g).
[0077] Next, the above-mentioned intensive heat residual components were subjected to elemental analysis according to the method specified in JIS M8819 to measure the mass ratio P1 (%) of carbon. The residual carbon ratio P2 (mass %) can be calculated by the following formula (I).
[0078] [Number 1]
[0079]
[0080] When the carbon precursor and the volatile organic matter are mixed, the mass ratio of the carbon precursor to the volatile organic matter in the mixture is not particularly limited, and the mass ratio of the carbon precursor to the volatile organic matter is preferably 99:1 to 40:60. The mass ratio of the carbon precursor to the volatile organic matter in the above mixture is more preferably 97:3 to 40:60, further preferably 95:5 to 60:40, and particularly preferably 93:7 to 80:20. For example, if the volatile organic matter is 1 part by mass or more, the specific surface area can be sufficiently reduced. In addition, if the volatile organic matter is 60 parts by mass or less, the effect of reducing the specific surface area is unsaturated, and it is difficult to consume the volatile organic matter excessively, so it is industrially advantageous.
[0081] When the carbon precursor and the volatile organic matter are mixed, they may be mixed at any stage as long as it is before calcining the carbon precursor, and may be mixed before the above-mentioned primary pulverization step or after primary pulverization, classification and secondary pulverization.
[0082] The carbon precursor that becomes the raw material of the carbonaceous material of the present invention is the precursor of the carbonaceous material that supplies the carbon component when manufacturing the carbonaceous material, and can be widely selected from carbon precursors derived from plants, carbon precursors derived from minerals, carbon precursors derived from natural raw materials, and carbon precursors derived from synthetic raw materials, etc. From the viewpoint of reducing harmful impurities, the viewpoint of environmental protection, and the viewpoint of commerce, the carbonaceous material of the present invention is preferably based on a carbon precursor derived from plants, in other words, the carbon precursor that becomes the raw material of the carbonaceous material of the present invention is preferably derived from plants.
[0083] Examples of carbon precursors derived from minerals include petroleum-based and carbonaceous asphalts and carbon coke. Examples of carbon precursors derived from natural raw materials include carbonized products of natural fibers such as kapok and hemp, regenerated fibers such as rayon and viscose rayon, and semi-synthetic fibers such as acetate and triacetate. Examples of carbon precursors derived from synthetic raw materials include carbonized products of polyamides such as nylon, polyvinyl alcohols such as vinylon, polyacrylonitrile such as acryl, polyolefins such as polyethylene and polypropylene, polyurethanes, phenolic resins, and vinyl chloride resins.
[0084] The plant-derived carbon precursor can be produced by using a plant-derived carbon material (hereinafter also referred to as "plant-derived coke") as a raw material and subjecting it to activation, deashing, and the like.
[0085] Therefore, the method for producing the carbonaceous material of the present invention may include, for example, the following steps in addition to the above-mentioned steps of pulverizing, classifying and calcining:
[0086] (i) a step of subjecting the plant-derived carbon material to be the raw material to activation treatment; and / or
[0087] (ii) A step of deashing the plant-derived carbon material or the like serving as a raw material.
[0088] In addition, coke generally refers to a non-melting and softening carbon-rich powdery solid obtained by heating coal, but here it also refers to a non-melting and softening carbon-rich powdery solid obtained by heating an organic matter.
[0089] The plants that become the raw materials of plant-derived coke (hereinafter also referred to as "plant raw materials") are not particularly limited. As plant raw materials, coconut shells, coffee beans, tea leaves, sugar cane, fruits (such as oranges, bananas), rice straw, rice husks, hardwood, coniferous wood, bamboo can be exemplified. The examples include waste after the original purpose (such as used tea leaves) or a part of the plant raw materials (such as bananas and orange peels). These plant raw materials can be used alone or in combination of two or more. Among these plant raw materials, coconut shells are preferred from the viewpoint of easy acquisition in large quantities.
[0090] The coconut shell is not particularly limited, and examples thereof include coconut shells of oil palm (oil coconut), coconut, snake fruit, sea coconut, etc. These coconut shells may be used alone or in combination of two or more. Biomass waste generated in large quantities after coconut is used as a food, detergent raw material, biodiesel raw material, etc., namely coconut shells of coconut and oil palm are particularly preferred from the viewpoint of easy availability.
[0091] The method for producing plant-derived coke from a plant raw material is not particularly limited, and the plant raw material can be produced by, for example, heat-treating the plant raw material at a temperature of 300° C. or higher in an inert gas atmosphere (hereinafter also referred to as “preliminary calcination”).
[0092] The heat treatment temperature of the preliminary calcination is not particularly limited as long as it is 300°C or higher. If the heat treatment temperature of the preliminary calcination is too high, the coke may be highly crystallized, and subsequent pulverization may become difficult. Therefore, the heat treatment temperature of the preliminary calcination is usually 300°C to 1000°C, preferably 400°C to 900°C, and more preferably 500°C to 800°C.
[0093] The heat treatment time of the pre-calcination is not particularly limited. If the heat treatment time of the pre-calcination is too long, the coke may be highly crystallized, and subsequent pulverization may become difficult. Therefore, the heat treatment time of the pre-calcination is usually 1 to 24 hours, preferably 1.5 to 20 hours, and more preferably 2 to 15 hours.
[0094] Furthermore, it can also be obtained in the form of plant-derived coke (eg, coconut shell coke).
[0095] The carbonaceous material manufactured by the coke derived from plants can be doped with a large amount of active substances, and is therefore basically suitable as a carbonaceous material for electrochemical devices such as non-aqueous electrolyte secondary batteries. However, the coke derived from plants generally contains a large amount of metal elements (especially potassium, iron, etc.) contained in plant raw materials. If such an electrode of a carbonaceous material containing a large amount of metal elements is used for an electrochemical device, it is sometimes undesirable to electrochemical characteristics and safety. Therefore, the content of potassium elements, iron elements, etc. contained in the carbonaceous material is preferably reduced as much as possible.
[0096] In addition, the coke derived from plants, in addition to potassium and iron, also mostly contains alkali metals (such as sodium), alkaline earth metals (such as magnesium or calcium), transition metals (such as copper) and other elements (hereinafter, it is also collectively referred to as "ash"). When the electrode containing the carbonaceous material containing these metal elements is used for the negative electrode of a non-aqueous electrolyte secondary battery such as a lithium ion secondary battery, the impurities are dissolved in the electrolyte during the dedoping of the negative electrode, which has an undesirable effect on the battery performance, and it is possible to damage the reliability of the non-aqueous electrolyte secondary battery, so it is preferred to also reduce the content of these metals. In addition, by reducing the ash in the carbonaceous material, it is easy to suppress the pore occlusion of the carbonaceous material and improve the charge and discharge capacity of the battery.
[0097] Therefore, the content of ash (alkali metal elements, alkaline earth metal elements, transition metal elements, and other elements) in the plant raw material or the coke derived from the plant is preferably reduced in advance before calcining the carbon precursor in order to obtain the carbonaceous material. Here, reducing the content of ash in the plant raw material or the coke derived from the plant raw material is also referred to as "deashing" below. There is no particular limitation on the deashing method, and for example, a method (liquid phase deashing) in which the metal component is extracted and deashed using an acidic solution containing an inorganic acid such as hydrochloric acid, sulfuric acid, an organic acid such as acetic acid, formic acid, etc., and a method (gas phase deashing) of exposing to a high temperature gas phase containing a halogen compound such as hydrogen chloride to deash.
[0098] Liquid phase deashing can be implemented in any form of plant raw materials or coke derived from plants. Liquid phase deashing can be carried out, for example, by immersing plant raw materials or coke derived from plants in an acidic solution. The acidic solution is a mixture of an acid and an aqueous solution. As an acid, there is no particular limitation, and examples thereof include aqueous solutions of inorganic acids such as hydrochloric acid and sulfuric acid, and organic acids such as acetic acid, butyric acid, and citric acid. From the viewpoint of avoiding residual unwanted ions in the deashed material, as an acid, an organic acid is preferably used, and from the viewpoint of the efficiency of deashing, the economic efficiency such as the price of the acid, and the ease of waste liquid treatment after use, acetic acid and / or citric acid are more preferably used. As an aqueous solution, water, a mixture of water and a water-soluble organic solvent, etc., can be cited. As a water-soluble organic solvent, alcohols such as methanol, ethanol, propylene glycol, and ethylene glycol can be cited.
[0099] The acid concentration in the acid solution is not particularly limited. The deashing rate is affected by the acid concentration, so it is preferably in the range of 0.001 to 1 M, more preferably in the range of 0.002 to 0.9 M, and even more preferably in the range of 0.005 to 0.5 M. The amount of the acid solution used is also not particularly limited. It is preferably the degree to which the plant material or plant-derived coke to be immersed in the acid solution. For example, the mass of the acid solution relative to the mass of the plant material or plant-derived coke to be immersed is preferably 100 to 1000 mass%, more preferably 200 to 900 mass%, and even more preferably 250 to 800 mass%.
[0100] The temperature of liquid phase deliming may be determined according to the plant raw material or plant-derived coke to be delimed, and may be, for example, 10 to 120° C., preferably 20 to 100° C., and more preferably 25 to 95° C. If the deliming temperature is within the above range, deliming can be performed efficiently while suppressing a decrease in carbon content due to hydrolysis of organic matter constituting the plant.
[0101] The time of liquid phase deliming is not particularly limited, and can be, for example, 0.1 to 100 hours, preferably 0.2 to 50 hours, and more preferably 0.5 to 20 hours. Liquid phase deliming can be carried out continuously after the plant raw material or the coke derived from the plant is immersed in the acidic solution, or it can be carried out in multiple times while the acidic solution used for deliming is renewed. When liquid phase deliming is carried out in multiple times, the total deliming time is recorded as the liquid phase deliming time.
[0102] The apparatus used for liquid phase deashing is not particularly limited as long as it is an apparatus capable of immersing the plant raw material or plant-derived coke in an acidic solution. For example, a glass-lined stirring tank can be used.
[0103] Gas phase deashing can be implemented in any form of plant raw materials or coke derived from plants. Gas phase deashing can be carried out by, for example, heat treating plant raw materials or coke derived from plants in a gas phase containing halogen compounds. As halogen compounds, there are no particular limitations, such as fluorine, chlorine, bromine, iodine, hydrogen fluoride, hydrogen chloride, hydrogen bromide, iodine bromide, chlorine fluoride (ClF), iodine chloride (ICl), iodine bromide (IBr), bromine chloride (BrCl), etc. Compounds or mixtures thereof that produce these halogen compounds by thermal decomposition can also be used. From the viewpoint of supply stability and the stability of the halogen compounds used, the halogen compound is preferably hydrogen chloride.
[0104] Gas phase deashing can be carried out in a gas phase in which a halogen compound and an inert gas are mixed. The inert gas is not particularly limited as long as it is a gas that does not react with the deashed material (plant raw material or coke derived from plants) and the plant raw material or coke derived from plants after deashing at the deashing temperature. For example, nitrogen, helium, argon, krypton, or a mixed gas thereof can be cited. From the viewpoint of supply stability and economy, the inert gas is preferably nitrogen.
[0105] When gas phase deashing is performed in a gas phase in which a halogen compound and an inert gas are mixed, the mixing ratio of the halogen compound to the inert gas is not particularly limited as long as sufficient deashing can be achieved. For example, the amount of the halogen compound relative to the inert gas is preferably 0.01 to 10.0 volume %, more preferably 0.05 to 8.0 volume %, and even more preferably 0.1 to 5.0 volume %.
[0106] The temperature of gas phase deashing may be determined according to the plant raw material or plant-derived coke as the deashing object, and may be, for example, 500 to 1100° C., preferably 600 to 1050° C., more preferably 650 to 1000° C., and further preferably 850 to 1000° C. If the deashing temperature is too low, the deashing efficiency may be reduced, and deashing may not be performed sufficiently. If the deashing temperature is too high, activation may be caused by the halogen compound.
[0107] The time for gas phase deashing is not particularly limited, and is, for example, 5 to 300 minutes, preferably 10 to 200 minutes, and more preferably 15 to 150 minutes.
[0108] The supply rate (flow rate) of the gas phase in gas phase deashing is not particularly limited, and for example, it is preferably 1 ml / min or more, more preferably 5 ml / min or more, and further preferably 10 ml / min or more per 1 g of the plant raw material or plant-derived coke.
[0109] The device used in gas phase deashing is not particularly limited as long as it can heat the plant raw material or plant-derived coke while mixing it with the gas phase containing the halogen compound. For example, a fluidized furnace or a continuous or intermittent layer flow-through device using a fluidized bed or the like can be used.
[0110] In the case of gas phase deashing, after the heat treatment in the gas phase containing halogen compounds, heat treatment can be further performed in the absence of halogen compounds. Halogens are usually contained in plant raw materials or plant-derived coke by heat treatment in the gas phase containing halogen compounds. The halogens contained in the plant raw materials or plant-derived coke can be removed by heat treatment in the absence of halogen compounds. For example, after the heat treatment in the gas phase containing the aforementioned halogen compounds, the heat treatment is performed by blocking the supply of halogen compounds, thereby enabling the halogen to be removed. Specifically, the heat treatment in the absence of halogen compounds can be performed by heat treatment at 500°C to 1100°C, preferably 600°C to 1050°C, more preferably 650°C to 1000°C, and further preferably 850°C to 1000°C in an inert gas atmosphere not containing halogen compounds. The temperature of the heat treatment in the absence of halogen compounds is preferably the same as the temperature of the heat treatment in the gas phase containing halogen compounds, or is performed at a temperature higher than that. The time of the heat treatment in the absence of a halogen compound is also not particularly limited, but is preferably 5 to 300 minutes, more preferably 10 to 200 minutes, and even more preferably 10 to 100 minutes.
[0111] Liquid phase deashing and gas phase deashing in the present embodiment are treatments for removing ash such as potassium and iron contained in plant raw materials or coke derived from plants. The potassium content of the carbon precursor obtained after the liquid phase deashing treatment or the gas phase deashing treatment is preferably 1000ppm (0.1 weight %) or less, more preferably 500ppm or less, and further preferably 300ppm or less. The iron content of the carbon precursor obtained after the liquid phase deashing treatment or the gas phase deashing treatment is preferably 200ppm or less, more preferably 150ppm or less, and further preferably 100ppm or less. If the content of potassium and iron in the carbon precursor is below the above upper limit, when the obtained carbonaceous material is used for electrodes for electrochemical devices such as non-aqueous electrolyte secondary batteries, the dissolution of impurities in the electrolyte during dedoping can be reduced, which is preferred in terms of improving the performance and reliability of the electrochemical device.
[0112] When a plant raw material is used in liquid phase deashing or gas phase deashing, the plant raw material after liquid phase deashing or gas phase deashing can be pre-calcined by heat treatment at a temperature of 300° C. or higher in an inert gas atmosphere to produce plant-derived coke after liquid phase deashing or gas phase deashing. The heat treatment temperature and heat treatment time of the pre-calcination in this case are also as described above.
[0113] In addition, the average particle size of the plant raw material or plant-derived coke as the deashing object is not particularly limited. In the case of liquid phase deashing, from the viewpoint of easily separating the carbon precursor after deashing from the extract, the lower limit of the average particle size is preferably 500 μm or more, more preferably 1 mm or more, and further preferably 2 mm or more. The upper limit of the average particle size is preferably 40 mm or less, more preferably 35 mm or less, and further preferably 30 mm or less. In the case of gas phase deashing, if the average particle size is too small, it may be difficult to separate the gas phase containing potassium and the like removed by deashing, and the carbon precursor after deashing, so the lower limit of the average particle size is preferably 100 μm or more, more preferably 200 μm or more, and further preferably 400 μm or more. The upper limit of the average particle size is preferably 10000 μm or less, more preferably 8000 μm or less, and further preferably 5000 μm or less.
[0114] The carbonaceous material of the present invention can be obtained by subjecting the carbon precursor obtained through such treatment to primary pulverization, classification, secondary pulverization and calcination as described above.
[0115] In addition, in the present invention, by mixing two or more carbon precursors or carbonaceous materials having different physical properties (such as average particle size, particle size distribution, etc.), it is also possible to prepare the carbonaceous material of the present invention having a desired AE. In the case of preparing the carbonaceous material of the present invention having a desired AE by mixing two or more carbon precursors or carbonaceous materials, the type of the mixed carbon precursor or carbonaceous material and its mixing ratio can be appropriately determined according to the desired AE. In this case, at least one carbon precursor or carbonaceous material mixed is also preferably a carbon precursor or carbonaceous material obtained through the above-mentioned steps of primary pulverization, classification and secondary pulverization. At least one carbon precursor or carbonaceous material is a substance obtained through the above-mentioned steps, thereby making it easy to control the AE of the obtained carbonaceous material to a desired range.
[0116] When two or more carbon precursors or carbonaceous materials are mixed to prepare the carbonaceous material of the present invention, the amount of the carbon precursor or carbonaceous material produced by the above-mentioned primary crushing, classification and secondary crushing steps can be appropriately determined according to the physical properties of the carbon precursor or carbonaceous material used, and is based on the total mass of the final mixture of carbon precursors or carbonaceous materials, for example, 20% by mass or more. The upper limit of the amount of the carbon precursor or carbonaceous material produced by the above-mentioned primary crushing, classification and secondary crushing steps in the mixture of carbon precursors or carbonaceous materials is not particularly limited, and all of them can be carbon precursors or carbonaceous materials produced according to the above method.
[0117] [Electrodes for electrochemical devices]
[0118] The carbonaceous material of the present invention is suitable as a material for an electrode for an electrochemical device, particularly a negative electrode for an electrochemical device. By using the carbonaceous material of the present invention, the density of the obtained electrode can be increased, and the irreversible capacity can be reduced, so a small and high-capacity electrochemical device can be obtained. Electrochemical devices suitable for the use of the carbonaceous material of the present invention include secondary batteries such as lithium ion secondary batteries, nickel-hydrogen secondary batteries, nickel-cadmium secondary batteries, and capacitors such as double-layer capacitors. Among these, the electrochemical device can be particularly a non-aqueous electrolyte secondary battery (such as a lithium ion secondary battery, a sodium ion battery, a lithium sulfur battery, a lithium air battery, a fully solid battery, an organic free radical battery, etc.), and can be more particularly a lithium ion secondary battery.
[0119] The following is an explanation of the negative electrode for the electrochemical device of the present invention, taking the negative electrode for a non-aqueous electrolyte secondary battery as an example. The negative electrode of the present invention can be manufactured by coating the electrode mixture on a current collecting plate and forming an electrode active material layer on the current collecting plate. The electrode mixture can be obtained by adding an appropriate amount of a binder (adhesive), a conductive aid according to the situation, and a suitable solvent to the carbonaceous material of the present invention, and kneading. The electrode active material layer can be obtained by, for example, coating the electrode mixture on a current collecting plate, drying it, and then press-molding it. As a current collecting plate, for example, a metal plate can be used.
[0120] As long as the binder is a substance that does not react with the electrolyte, there is no particular limitation, and examples thereof include PVDF (polyvinylidene fluoride), polytetrafluoroethylene, and a mixture of SBR (styrene butadiene rubber) and CMC (carboxymethyl cellulose). Among these, for PVDF, the PVDF attached to the surface of the active material hinders the movement of lithium ions less, and it is easy to obtain good input-output characteristics, so it is preferred. As a binder, one kind can be used, or two or more kinds can be used in combination. The amount of the binder added can be appropriately selected according to the type of binder used, for example, preferably 1 to 20% by mass, more preferably 1 to 15% by mass. For example, in the case of a PVDF-based binder, it is preferably 3 to 13% by mass, more preferably 3 to 10% by mass. Here, the amount of the binder added is calculated as the amount of active material (carbonaceous material) + the amount of adhesive + the amount of conductive additive = 100% by mass. When the amount of the binder added is within the above range, an increase in resistance in the obtained electrode can be suppressed, the internal resistance of the battery can be reduced, and bonding between carbonaceous material particles in the electrode and bonding between the carbonaceous material and the current collector can be improved.
[0121] The solvent can be appropriately selected according to the type of binder used. As a solvent, one kind can be used, or two or more kinds can be used in combination. For example, when PVDF is used as a binder, from the viewpoint of dissolving PVDF and easily obtaining a slurry, it is preferred to use a polar solvent such as N-methylpyrrolidone (NMP). When SBR or the like is used as a binder, the binder can be used in the form of an aqueous emulsion. When CMC is used as a binder, the binder can be dissolved in a solvent such as water and used.
[0122] For example, water is used as a solvent, and a mixture of SBR and CMC and two or more binders are often used in combination. In this method, when two or more binders are used, the total amount of binders added is preferably 0.5 to 5% by mass, and more preferably 1 to 4% by mass. Here, the amount of binder added is calculated as the amount of active material (carbonaceous material) + the amount of adhesive + the amount of conductive additive = 100% by mass.
[0123] Furthermore, in order to impart high conductivity, a conductive aid can be added as needed during the preparation of the electrode mixture. As a conductive aid, conductive carbon black, vapor grown carbon fiber (VGCF), nanotubes, etc. can be used. The amount of the conductive aid added varies depending on the type of conductive aid used, preferably 0.5 to 10% by weight, more preferably 0.5 to 7% by weight, and further preferably 0.5 to 5% by weight. Here, the amount of the conductive aid added is calculated as the amount of active material (carbonaceous material) + the amount of binder + the amount of conductive aid = 100% by weight. If the amount of the conductive aid added is within the above range, the conductivity is easily improved, and the dispersion of the conductive aid in the electrode mixture also becomes good.
[0124] The electrode active material layer is usually formed on both sides of the current collector, but it can also be formed on a single side of the current collector as needed. The average single-sided thickness of the electrode active material layer is preferably 10 to 80 μm, more preferably 20 to 75 μm, and further preferably 20 to 60 μm. If the thickness of the electrode active material layer is above the above lower limit, the proportion of the current collector, separator, etc. in the secondary battery can be small, so it is preferred from the perspective of easily increasing the capacity of the battery. If the thickness of the electrode active material layer is below the above upper limit, the wider the electrode area relative to the counter electrode, the more beneficial it is to improve the input-output characteristics, so it is preferred from the perspective of easily improving the input-output characteristics.
[0125] Furthermore, lithium pre-doping may be performed by a known method in order to reduce the irreversible capacity of the obtained electrode active material layer.
[0126] [Electrochemical equipment]
[0127] The electrochemical device of the present invention includes the negative electrode for an electrochemical device of the present invention, has a high electrode density, a small irreversible capacity, and a high capacity.
[0128] For example, when the electrochemical device of the present invention is a nonaqueous electrolyte secondary battery, other materials constituting the battery such as the positive electrode material, separator and electrolyte solution are not particularly limited, and various materials conventionally used or proposed in nonaqueous electrolyte secondary batteries can be used.
[0129] For example, as the positive electrode material, a layered oxide system (expressed as LiMO2, M is a metal: such as LiCoO2, LiNiO2, LiMnO2, or LiNi x Co y Mo z O2 (here, x, y, z represent the composition ratio)), olivine system (LiMPO4, M is a metal: such as LiFePO4, etc.), spinel system (LiM2O4, M is a metal: such as LiMn2O4, etc.) composite metal oxygen element compounds. As the positive electrode material, one of these oxygen element compounds can be used, or two or more can be mixed and used as needed. These positive electrode materials are molded together with a suitable binder and a carbonaceous material for imparting conductivity to the electrode to form a layer on a conductive current collecting material, thereby making it possible to manufacture a positive electrode.
[0130] The non-aqueous solvent type electrolyte used in combination with the positive electrode and the negative electrode can generally be obtained by dissolving the electrolyte in a non-aqueous solvent. As the non-aqueous solvent, organic solvents such as propylene carbonate, ethylene carbonate, dimethyl carbonate, diethyl carbonate, dimethoxyethane, diethoxyethane, γ-butyrolactone, tetrahydrofuran, 2-methyltetrahydrofuran, cyclopentane, or 1,3-dioxolane can be cited. As an organic solvent, one organic solvent can be used, or two or more organic solvents can be used in combination. As an electrolyte, for example, LiClO4, LiPF6, LiBF4, LiCF3SO3, LiAsF6, LiCl, LiBr, LiB(C6H5)4, or LiN(SO3CF3)2 can be cited.
[0131] In general, a non-aqueous electrolyte secondary battery can be manufactured by placing the positive electrode and the negative electrode opposite to each other via a separator as needed and immersing them in an electrolyte. As a separator, a non-woven fabric commonly used in secondary batteries or a liquid-permeable separator containing other porous materials can be used. Instead of a separator or together with a separator, a solid electrolyte containing a polymer gel impregnated with an electrolyte can also be used.
[0132] The carbonaceous material of the present invention is suitable as a carbonaceous material for batteries (typically non-aqueous electrolyte secondary batteries for vehicle driving) carried on vehicles such as automobiles. In the present invention, the vehicle generally refers to a vehicle known as an electric vehicle, a hybrid vehicle of a fuel cell and an internal combustion engine, etc., which can be set as an object without special restrictions, at least having a power supply device with the above-mentioned battery, an electric drive mechanism driven by a power supply from the power supply device, and a control device for controlling it. The vehicle can further have a power generation brake, a regenerative brake, and a mechanism for converting the energy used in braking into electricity to charge the aforementioned non-aqueous electrolyte secondary battery.
[0133] Example
[0134] The present invention is specifically described below by examples, but they do not limit the scope of the present invention. It should be noted that the following describes the determination methods of the physical property values of the carbonaceous material, but the physical property values described in this specification, including the examples, are based on the values obtained by the following methods.
[0135] (1) Average particle size D 50 and particle size distribution index D 50 / D 10 Determination and calculation of
[0136] Average particle size D of carbon precursor and carbonaceous material 50 (Particle size distribution) is determined by a laser scattering method as described below. Samples of the carbon precursor and carbonaceous material prepared in the examples and comparative examples described later are placed in an aqueous solution containing 0.3% by mass of a surfactant ("Toriton X100" manufactured by Wako Pure Chemical Industries, Ltd.), treated with an ultrasonic scrubber for more than 10 minutes, and dispersed in the aqueous solution. The particle size distribution is determined using this dispersion. The particle size distribution is determined using a particle size and particle size distribution measuring instrument ("Microtrack MT3000" manufactured by Nikkiso Co., Ltd.), with the solvent refractive index set to 1.33 and the particle permeability set to absorption. The particle size at which the cumulative volume reaches 50% is recorded as the average particle size D 50 .
[0137] In addition, the particle size at which the cumulative volume reaches 10% is recorded as D 10 , the particle size distribution index D is calculated using the following formula 50 / D 10 .
[0138] Particle size distribution index D 50 / D 10 = Average particle size D 50 / D 10 .
[0139] (2) Determination of BET specific surface area
[0140] In this specification, the specific surface area of the carbonaceous material and the carbon precursor is determined by the BET method (nitrogen adsorption BET three-point method) (BET specific surface area). The approximate formula derived from the BET formula is described below.
[0141] [Number 2]
[0142] p / [v(p0-p)]=(1 / v m c)+[(c-1) / v m c](p / p0)
[0143] Using the above approximate formula, v was calculated by the three-point method using nitrogen adsorption at liquid nitrogen temperature. m The specific surface area of the sample was calculated using the following formula.
[0144] [Number 3]
[0145]
[0146] At this time, v m is the amount of adsorption required to form a monolayer on the sample surface (cm 3 / g), v is the measured adsorption capacity (cm 3 / g), p0 is the saturated vapor pressure, p is the absolute pressure, c is a constant (reflecting the adsorption heat), and N is the Avogadro constant of 6.022×10 23 , a(nm 2 ) is the area occupied by the adsorbate molecules on the sample surface (cross-sectional area occupied by the molecules).
[0147] More specifically, the amount of nitrogen adsorbed on a sample at liquid nitrogen temperature can be measured as follows, for example, using the "BELL Sorb Mini" manufactured by BELL Corporation of Japan. The sample is filled in a sample tube, and the sample tube is temporarily depressurized while being cooled to -196°C, and then nitrogen (purity 99.999%) is adsorbed on the sample at a desired relative pressure. The amount of nitrogen adsorbed on the sample when the equilibrium pressure is reached at each desired relative pressure is recorded as the adsorbed gas amount v.
[0148] (3) Determination of flow energy AE during ventilation
[0149] The measurement was performed using a powder rheometer FT4 manufactured by Freeman Technolog Co., Ltd. In a measuring container (50 mm in diameter, 160 cm in volume) 3 ) is filled with carbonaceous material to measure AE to a flat mouth (120 mL), and after being set on the device, air is ventilated from the bottom of the device at a ventilation rate of 2 mm / sec, and a knife (radius: 48 mm) is rotated at a blade tip speed of 100 mm / sec while entering. At this time, the spiral angle α of the knife tip movement is 5°. The movement energy of the knife corresponding to the knife height is calculated according to the following formula:
[0150] AE=T / (Rtanα)+F
[0151] Calculate the ventilation flow energy (AE).
[0152] (4) Average interplanar spacing d of (002) planes by X-ray diffraction 002
[0153] Using "MiniFlexII manufactured by Rigaku Co., Ltd.", the carbonaceous material powder was filled on the sample stand, and the CuKα line monochromated by the Ni filter was used as the line source to obtain the X-ray diffraction pattern. The peak position of the diffraction pattern was obtained by the centroid method (a method of obtaining the centroid position of the diffraction line and the peak position at the corresponding 2θ value), and the diffraction peak of the (111) plane of high-purity silicon powder was used as a standard substance for correction. The wavelength λ of the CuKα line was set to 0.15418nm, and d002 was calculated by the Bragg formula (Formula (IV)) described below.
[0154] [Number 4]
[0155]
[0156] 1. Example 1
[0157] (1) Preparation of carbon precursor
[0158] <Preparation Example 1>
[0159] Gas phase deashing: Coconut shells were dry distilled at 500°C and then crushed to obtain coconut shell coke with an average particle size of about 2 mm. 100 g of the coconut shell coke was subjected to halogen heat treatment at 900°C for 30 minutes while nitrogen containing 1% by volume of hydrogen chloride gas was supplied at a flow rate of 18 L / min. Thereafter, only the supply of hydrogen chloride gas was stopped, and nitrogen gas was supplied at a flow rate of 18 L / min while heat treatment was further performed at 900°C for 30 minutes, thereby performing gas phase deacidification treatment to obtain a carbon precursor.
[0160] (2) Preparation of carbonaceous materials
[0161] Primary pulverization step: The carbon precursor obtained in Preparation Example 1 was pulverized using a fine grinder SF5 (manufactured by Japan Carbon Coke) to an average particle size of D 50 The particles were crushed to 4.1 μm.
[0162] Classification step: The carbon precursor after the primary pulverization was classified using LabClarksill N-01 (manufactured by Seishin Enterprise Co., Ltd.) so that the volume ratio of particles of 1 μm or less was 3.3 volume %.
[0163] Secondary pulverization step: The classified carbon precursor is pulverized using the same fine mill SF5ル as used in the primary pulverization to an average particle size of D 50 The carbon precursor was obtained by crushing the particles to 2.8 μm. 50 / D 10 It is 3.9.
[0164] Calcination step: Mix 6.4 g of the carbon precursor prepared above with 0.6 g of polystyrene (produced by Sekisui Chemicals Co., Ltd., average particle size 400 μm, residual carbon rate 1.2%). Place 7 g of the mixture in a graphite chamber in such a way that the sample layer height reaches about 3 mm. In a tubular furnace manufactured by Motoyama Co., Ltd., heat it to 1250°C at a rate of 10°C per minute at a nitrogen flow rate of 6 L per minute, maintain it for 10 minutes, and cool it naturally. Confirm that the temperature in the furnace has dropped below 200°C, and take out the carbonaceous material from the furnace. Measure the average particle size D of the obtained carbonaceous material. 50 , D 50 / D 10 , BET specific surface area, AE and average interplanar spacing d 002 The results are shown in Table 1.
[0165] 2. Example 2
[0166] Primary pulverization step: The carbon precursor obtained in Preparation Example 1 was pulverized using a fine grinder SF5 (manufactured by Japan Carbon Coke) to an average particle size of D 50 The particle size is reduced to 8.9 μm.
[0167] Classification step: The carbon precursor after the primary pulverization was classified using LabClarksill N-01 (manufactured by Seishin Enterprise Co., Ltd.) so that the volume ratio of particles of 1 μm or less was 0 volume %.
[0168] Secondary pulverization step: The classified carbon precursor is milled using the same ball mill as that used in the primary pulverization to obtain an average particle size of D 50 The carbon precursor was obtained by crushing the particles to 2.9 μm. 50 / D 10 It is 3.9.
[0169] After secondary pulverization, calcination treatment was carried out in the same manner as in Example 1 to obtain a carbonaceous material. The average particle size D of the obtained carbonaceous material was measured. 50 , D 50 / D 10 , BET specific surface area, AE and average interplanar spacing d 002 The results are shown in Table 1.
[0170] 3. Example 3
[0171] Primary pulverization step: The carbon precursor obtained in Preparation Example 1 was pulverized using a fine grinder SF5 (manufactured by Japan Carbon Coke) to an average particle size of D 50 The particles were crushed to 102 μm.
[0172] Classification step: The carbon precursor after the primary pulverization was classified using LabClarksill N-01 (manufactured by Seishin Enterprise Co., Ltd.) so that the volume ratio of particles of 1 μm or less was 0 volume %.
[0173] Secondary pulverization step: The classified carbon precursor is milled using the same ball mill as that used in the primary pulverization to obtain an average particle size of D 50 The carbon precursor was obtained by crushing the particles to 2.8 μm. 50 / D 10 is 3.1.
[0174] After secondary pulverization, calcination treatment was carried out in the same manner as in Example 1 to obtain a carbonaceous material. The average particle size D of the obtained carbonaceous material was measured. 50 , D 50 / D 10 , BET specific surface area, AE and average interplanar spacing d 002 The results are shown in Table 1.
[0175] 4. Comparative Example 1
[0176] The carbon precursor obtained in Preparation Example 1 was pulverized to an average particle size of 2.5 μm using a refiner SF5 (produced by Nippon Tanko Co., Ltd.).
[0177] Thereafter, without classification and secondary pulverization, calcination treatment was performed in the same manner as in Example 1 to obtain a carbonaceous material. The average particle size D of the obtained carbonaceous material was measured. 50 , D 50 / D 10 , BET specific surface area, AE and average interplanar spacing d 002 The results are shown in Table 1.
[0178] 5. Comparative Example 2
[0179] The carbon precursor obtained in the same manner as in the primary pulverization of Comparative Example 1 was classified using LabClarksill N-01 (manufactured by Seishin Enterprise Co., Ltd.) so that the volume ratio of particles of 1 μm or less became 6.1 volume %.
[0180] Next, the classified carbon precursor was milled into a ball mill with an average particle size of D 50 The particle size of the particles was crushed to 1.4 μm. 50 / D 10 After secondary pulverization, the carbonaceous material was calcined in the same manner as in Example 1 to obtain the carbonaceous material. The average particle size D of the obtained carbonaceous material was measured.50 , D 50 / D 10 , BET specific surface area, AE and average interplanar spacing d 002 The results are shown in Table 1.
[0181] 6. Comparative Example 3
[0182] Primary pulverization step: The carbon precursor obtained in Preparation Example 1 was pulverized using a fine grinder SF5 (manufactured by Japan Carbon Coke) to an average particle size of D 50 The particles were crushed to 310 μm.
[0183] Classification step: The carbon precursor after the primary pulverization was classified using LabClarksill N-01 (manufactured by Seishin Enterprise Co., Ltd.) so that the volume ratio of particles of 1 μm or less was 0 volume %.
[0184] Secondary pulverization step: The classified carbon precursor is milled using the same ball mill as that used in the primary pulverization to obtain an average particle size of D 50 The carbon precursor was obtained by crushing the particles to 2.6 μm. 50 / D 10 is 1.9.
[0185] After secondary pulverization, calcination treatment was carried out in the same manner as in Example 1 to obtain a carbonaceous material. The average particle size D of the obtained carbonaceous material was measured. 50 , D 50 / D 10 , BET specific surface area, AE and average interplanar spacing d 002 The results are shown in Table 1.
[0186] 7. Comparative Example 4
[0187] Primary pulverization step: The carbon precursor obtained in Preparation Example 1 was pulverized using a fine grinder SF5 (manufactured by Japan Carbon Coke) to an average particle size of D 50 The particle size is reduced to 8.9 μm.
[0188] Classification step: The carbon precursor after the primary pulverization was classified using LabClarksill N-01 (manufactured by Seishin Enterprise Co., Ltd.) so that the volume ratio of particles of 1 μm or less was 0 volume %.
[0189] Thereafter, the carbonaceous material was calcined in the same manner as in Example 1 without secondary pulverization. The average particle size D of the obtained carbonaceous material was measured. 50 , D 50 / D 10 , BET specific surface area, AE and average interplanar spacing d 002 The results are shown in Table 1.
[0190] 8. Comparative Example 5
[0191] Primary pulverization step: The carbon precursor obtained in Preparation Example 1 was pulverized using a fine grinder SF5 (manufactured by Japan Carbon Coke) to an average particle size of D 50 The particles were crushed to 25 μm.
[0192] Classification step: The carbon precursor after the primary pulverization was classified using LabClarksill N-01 (manufactured by Seishin Enterprise Co., Ltd.) so that the volume ratio of particles of 1 μm or less was 0 volume %.
[0193] Thereafter, the carbonaceous material was calcined in the same manner as in Example 1 without secondary pulverization. The average particle size D of the obtained carbonaceous material was measured. 50 , D 50 / D 10 , BET specific surface area, AE and average interplanar spacing d 002 The results are shown in Table 1.
[0194] 9. Comparative Example 6
[0195] The carbon precursor obtained in Example 2 was prepared by using LabClark N-01 (manufactured by Seishin Enterprise Co., Ltd.) 50 The particles are graded to 3.4 μm.
[0196] Thereafter, a calcination treatment was performed in the same manner as in Example 1 to obtain a carbonaceous material. The average particle size D of the obtained carbonaceous material was measured. 50 , D 50 / D 10 , BET specific surface area, AE and average interplanar spacing d 002 The results are shown in Table 1.
[0197] 10. Comparative Example 7
[0198] The carbon precursor obtained in Comparative Example 5 was prepared by using LabClarkSial N-01 (manufactured by Seishin Enterprise Co., Ltd.) 50 The particle size was classified to 51.0 μm.
[0199] Thereafter, a calcination treatment was performed in the same manner as in Example 1 to obtain a carbonaceous material. The average particle size D of the obtained carbonaceous material was measured. 50 , D 50 / D 10 , BET specific surface area, AE and average interplanar spacing d 002 The results are shown in Table 1.
[0200] 11. Comparative Example 8
[0201] Primary pulverization step: The carbon precursor obtained in Preparation Example 1 was pulverized using a fine grinder SF5 (manufactured by Japan Carbon Coke) to an average particle size of D 50The particles were crushed to 4.1 μm.
[0202] Classification step: The carbon precursor after the primary pulverization was classified using LabClarksill N-01 (manufactured by Seishin Enterprise Co., Ltd.) so that the volume ratio of particles of 1 μm or less was 3.3 volume %.
[0203] Secondary pulverization step: The classified carbon precursor is milled using the same ball mill as that used in the primary pulverization to obtain an average particle size of D 50 The carbon precursor was obtained by crushing the particles to 0.9 μm. 50 / D 10 is 2.2.
[0204] After secondary pulverization, calcination treatment was carried out in the same manner as in Example 1 to obtain a carbonaceous material. The average particle size D of the obtained carbonaceous material was measured. 50 , D 50 / D 10 , BET specific surface area, AE and average interplanar spacing d 002 The results are shown in Table 1.
[0205] 12. Example 4
[0206] Mixing: The carbon precursor of Example 2 and the carbon precursor of Comparative Example 4 were mixed in a mass ratio of 1:1 to obtain a mixture of carbon precursors.
[0207] Polystyrene was added to the obtained carbon precursor mixture in the same manner as in Example 1, and calcination was performed to obtain a carbonaceous material. The average particle size D of the obtained carbonaceous material was measured. 50 , D 50 / D 10 , BET specific surface area, AE and average interplanar spacing d 002 The results are shown in Table 1.
[0208] 13. Example 5
[0209] Mixing: The carbon precursor of Example 2 and the carbon precursor of Comparative Example 5 were mixed in a mass ratio of 1:1 to obtain a mixture of carbon precursors.
[0210] Polystyrene was added to the obtained carbon precursor mixture in the same manner as in Example 1, and calcination was performed to obtain a carbonaceous material. The average particle size D of the obtained carbonaceous material was measured. 50 , D 50 / D 10 , BET specific surface area, AE and average interplanar spacing d 002 The results are shown in Table 1.
[0211] 14. Example 6
[0212] Mixing: The carbon precursor of Example 2 and the carbon precursor of Comparative Example 7 were mixed in a mass ratio of 1:1 to obtain a mixture of carbon precursors.
[0213] Polystyrene was added to the obtained carbon precursor mixture in the same manner as in Example 1, and calcination was performed to obtain a carbonaceous material. The average particle size D of the obtained carbonaceous material was measured. 50 , D 50 / D 10 , BET specific surface area, AE and average interplanar spacing d 002 The results are shown in Table 1.
[0214] 15. Comparative Example 9
[0215] Mixing: The carbon precursor of Comparative Example 2 and the carbon precursor of Comparative Example 4 were mixed at a mass ratio of 1:1 to obtain a mixture of carbon precursors.
[0216] Polystyrene was added to the obtained carbon precursor mixture in the same manner as in Example 1, and calcination was performed to obtain a carbonaceous material. The average particle size D of the obtained carbonaceous material was measured. 50 , D 50 / D 10 , BET specific surface area, AE and average interplanar spacing d 002 The results are shown in Table 1.
[0217] 16. Comparative Example 10
[0218] Primary pulverization step: The carbon precursor obtained in Preparation Example 1 was pulverized using a fine grinder SF5 (manufactured by Japan Carbon Coke) to an average particle size of D 50 The particles were crushed to 4.1 μm.
[0219] Classification step: The carbon precursor after the primary pulverization was classified using LabClarksill N-01 (manufactured by Seishin Enterprise Co., Ltd.) so that the volume ratio of particles of 1 μm or less was 3.3 volume %.
[0220] Secondary pulverization step: The classified carbon precursor is milled using the same ball mill as that used in the primary pulverization to obtain an average particle size of D 50 The carbon precursor was obtained by crushing the particles to 1.2 μm. 50 / D 10 is 2.5.
[0221] After secondary pulverization, calcination treatment was carried out in the same manner as in Example 1 to obtain a carbonaceous material. The average particle size D of the obtained carbonaceous material was measured. 50 , D 50 / D 10 , BET specific surface area, AE and average interplanar spacing d 002 The results are shown in Table 1.
[0222] 17. Example 7
[0223] Mixing: The carbon precursor of Comparative Example 4 and the carbon precursor of Comparative Example 10 were mixed at a mass ratio of 55:45 to obtain a mixture of carbon precursors.
[0224] Polystyrene was added to the obtained carbon precursor mixture in the same manner as in Example 1, and calcination was performed to obtain a carbonaceous material. The average particle size D of the obtained carbonaceous material was measured. 50 , D 50 / D 10 , BET specific surface area, AE and average interplanar spacing d 002 The results are shown in Table 1.
[0225]
[0226] The carbonaceous materials obtained in the examples and comparative examples were used to evaluate battery characteristics according to the following methods.
[0227] <Electrode production and electrode status confirmation>
[0228] 96.2 parts by mass of each carbonaceous material obtained in the examples and comparative examples, 2 parts by mass of conductive carbon black ("Super-P (registered trademark)" manufactured by TIMCAL), 1 part by mass of CMC, 0.8 part by mass of SBR and water were mixed to obtain slurry. The obtained slurry was coated on copper foil, dried and pressed to obtain a negative electrode (negative electrode layer).
[0229] <Electrode density>
[0230] The thickness of the negative electrode layer was determined by measuring the thickness of the produced negative electrode layer with a micrometer and subtracting the thickness of the current collector from the thickness of the negative electrode layer.
[0231] Electrode density (g / cm 3 ) is set as the mass (g) of the carbonaceous material mixed in each slurry divided by the volume (cm2) of the negative electrode layer produced when the negative electrode layer is produced. 3 ) and the value obtained (g / cm 3 ). It should be noted that the volume of the negative electrode layer was calculated using the thickness of the negative electrode layer and the diameter of the negative electrode layer (14 mm). When an evaluable electrode can be produced, the electrode state is evaluated as ○, and when an electrode cannot be evaluated due to agglomeration, bubbles, shedding of the negative electrode layer, etc. during electrode production, the electrode state is evaluated as ×.
[0232] <Measurement of charge capacity, discharge capacity, charge and discharge efficiency, and initial DC resistance>
[0233] Each electrode prepared as above was used as the working electrode, and metallic lithium was used as the counter electrode and reference electrode. As the solvent, a mixture of ethylene carbonate and methyl ethyl carbonate (volume ratio 3:7) was used. 1 mol / L of LiPF6 was dissolved in the solvent and used as an electrolyte. Glass fiber nonwoven fabric was used as the isolation membrane. Coin cell batteries were each prepared in a glove box under an argon atmosphere.
[0234] For the lithium ion secondary battery of the above-mentioned structure, a charge and discharge test device (manufactured by Toyo System Co., Ltd., "TOSCAT") was used to carry out a charge and discharge test. The initial DC resistance was set to the resistance value generated when 0.5 mA was circulated for 3 seconds. Lithium doping was carried out at a rate of 70 mA / g relative to the mass of the active material, and doping was performed until the potential relative to the lithium reached 1 mV. Furthermore, a constant voltage of 1 mV was applied to the lithium potential for 8 hours to terminate the doping. The capacity (mAh / g) at this time was recorded as the charging capacity. Next, dedoping was carried out at a rate of 70 mA / g relative to the mass of the active material until the potential relative to the lithium reached 2.5 V, and the capacity discharged at this time was recorded as the discharge capacity. Discharge capacity × electrode density is recorded as volume capacity. The percentage of discharge capacity / charge capacity is recorded as the charge and discharge efficiency, which is an indicator of the utilization efficiency of lithium ions in the battery.
[0235] [Table 2]
[0236]
Claims
1. A carbonaceous material for an electrochemical device having a specific surface area of 2 m2 as measured by the BET method 2 / g or more and 18m 2 / g or less, and the flow energy AE during ventilation measured by a powder rheometer is 40mJ or more and 210mJ or less, The average particle size D at which the cumulative volume from the fine particle side reaches 50% in the particle size distribution measured by the laser scattering method. 50 The particle size D is 1 μm or more and 50 μm or less and is based on 10% of the cumulative volume calculated from the microparticle side. 10 The average particle size D 50 The particle size distribution index D 50 / D 10 It is above 1.
9.
2. The carbonaceous material according to claim 1, wherein The average interplanar spacing d of the (002) planes calculated using the Bragg formula based on wide-angle X-ray diffraction 002 It is above 0.36nm.
3. The carbonaceous material according to claim 1 or 2, wherein Carbonaceous materials are derived from plants. 4 . A negative electrode for an electrochemical device, comprising the carbonaceous material according to claim 1 . 5 . An electrochemical device comprising the negative electrode for an electrochemical device according to claim 4 .
6. A method for producing a carbonaceous material, which is the method for producing a carbonaceous material according to any one of claims 1 to 3, The manufacturing method comprises: A step of subjecting the carbon precursor or the calcined carbon precursor to a primary pulverization; A step of classifying the once pulverized carbon precursor or the calcined carbon precursor; and a step of secondary pulverizing the classified carbon precursor or the calcined carbon precursor; and The step of calcining the carbon precursor, In the first pulverization step, the average particle size D 50 The carbon precursor or the calcined product of the carbon precursor is crushed to a size of 2.7 μm or more and 300 μm or less. In the classification step, the carbon precursor or the calcined product of the carbon precursor after the primary pulverization is classified so that the content of particles having a particle size of 1 μm or less is 6 volume % or less, In the secondary pulverization step, the average particle size D 50 The particle size D is 1 μm or more and 50 μm or less and accounts for 10% of the total volume. 10 The average particle size D 50 The particle size distribution index D 50 / D 10 The classified carbon precursor or the calcined product of the carbon precursor is pulverized so as to reach 1.9 or more.
Citation Information
Patent Citations
Carbonaceous material for nonaqueous electrolyte secondary battery, negative electrode and nonaqueous electrolyte secondary battery
JP2017073325A
Carbonaceous material for non-aqueous electrolyte secondary battery, negative electrode for non-aqueous electrolyte secondary battery, non-aqueous electrolyte secondary battery, and method for producing carbonaceous material for non-aqueous electrolyte secondary battery
CN108140836A
Carbonaceous substance for electrode material
JP2006269961A
Negative electrode material for lithium ion secondary battery and lithium ion secondary battery
JP2014089887A